Components of the ice age circulation - Rind, D. (1987)
The effects of ice age boundary conditions on atmospheric dynamics and regional climate patterns are investigated using four GCM simulations. Particular consideration is given to sea surface temperature-sea ice distribution, the appearance of land ice, and the increased elevation of land ice. It is observed that the ice-age sea surface temperature stabilizes the atmosphere over the oceans, increases the frequency of storm tracking through central North America, and amplifies transient eddy energy without increasing baroclinic generation. It is detected that low-elevation ice generates low pressure over eastern North America and southern Europe in winter, while increasing cloud cover and cooling the land in summer. Elevation of the ice sheets cools the land in winter, further intensifies storms off northeastern North America, induces subsidence warming downstream of the European ice sheets in summer, and increases the transient and stationary eddy energy through increased baroclinicity.